A Comparative Study Between Arthur Miller's Death Of A Salesman And August Wilson's Fences. (مجلة ديالى للبحوث الانسانية, 2022)
A Comparative Study Between Arthur Miller's Death Of A Salesman And August Wilson's Fences.           Arthur Miller's Death Of A Salesman (1949 Pulitzer Prize) portrays the life of an American family in the forties of the previous century. Willy Loman, the protagonist, is a traveling salesman in his sixties. He believes in the attractiveness of personality and popularity as a secret of success. He victimizes his son Biff, who was an outstanding football athlete in the high school with three scholarships from three different universities, by his (Willy's) adherence to his wrong philosophy and the past. The same thing goes for Troy Maxson, the protagonist of August Wilson's Fences (1987 Pulitzer Prize) which portrays the life of an African-American family in the fifties of the previous century. Troy is a former star athlete who turns to be a sanitation garbage collector believing that he has been segregated by the society. He victimizes his son Cory, a promising football player in the high school, preventing him from getting college football scholarship by his (Troy's) adherence to the past and his wrong belief. Yet Rose Maxson, the loyal wife and caring mother, manages to maintain her family together following Linda Loman's steps through patience and forgiveness.